2012
DOI: 10.1136/amiajnl-2011-000656
|View full text |Cite
|
Sign up to set email alerts
|

Translating Mendelian and complex inheritance of Alzheimer's disease genes for predicting unique personal genome variants

Abstract: ObjectiveAlthough trait-associated genes identified as complex versus single-gene inheritance differ substantially in odds ratio, the authors nonetheless posit that their mechanistic concordance can reveal fundamental properties of the genetic architecture, allowing the automated interpretation of unique polymorphisms within a personal genome.Materials and methodsAn analytical method, SPADE-gen, spanning three biological scales was developed to demonstrate the mechanistic concordance between Mendelian and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…We summarize the overlap and functional similarity between detected pathways from the three methods and the GS in Table 2 . Functional similarity between GO-BP was determine at a conservative cutoff of 0.7 using information theoretic similarity (ITS) methods we previously validated ( Gardeux et al , 2014a , b ; Li et al , 2012 ; Regan et al , 2012 ; Tao et al , 2007 ).…”
Section: Methodsmentioning
confidence: 99%
“…We summarize the overlap and functional similarity between detected pathways from the three methods and the GS in Table 2 . Functional similarity between GO-BP was determine at a conservative cutoff of 0.7 using information theoretic similarity (ITS) methods we previously validated ( Gardeux et al , 2014a , b ; Li et al , 2012 ; Regan et al , 2012 ; Tao et al , 2007 ).…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that a GO-ITS score ≥ 0.7 robustly corresponds to highly similar GO terms using different computational biological validations: protein interaction [27, 28], human genetics [29], and Genome-Wide Association Studies [30]. GO-ITS was calculated on each distinct pair among the 3234 GO terms of size ≥15 and ≤500, leading to 10,458,756 pairs of which 59,577 have a GO-ITS ≥ 0.7 (≈5.6 out of 1,000).…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that an ITS score ≥ 0.7 robustly corresponds to highly similar GO terms using different computational biological validations: protein interaction [22,23], human genetics [24], and Genome-Wide Association Studies [25]. …”
Section: Methodsmentioning
confidence: 99%